Strike, under the Industrial Relations Act 1967. / Haslina Hassan - Hassan, Haslina (Faculty of Law, 1986)
The main purpose of the study of strike under the Industrial Relations Act 1967, is an attempt to analyse the statutory provisions provided in the Industrial Relations Act 1967 concerning the legality and the lawfulness of a strike action. Apart from the provisions of the Act, regards have also been given to the common law provisions in an attempt to compare and to differentiate the sanctions given by both courts and statutes. In considering the other forms of industrial action which imminent similarities with strike action, it is the most potent and final attempt by the workers to make demands on the employers on subject matters that are refused to be negotiated on by the employers in other circumstances. Considerations will also be given the question of whether a trade union of workers has a right to strike.